URGENSI PSIKOLOGI AGAMA (SUATU PERSPEKTIF BARU) - Rusnawati Rusnawati (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
Psychology is a science that examines and studies human attitudes and behavior as a description of the psychological symptoms that are behind it, because the soul is abstract, then to study it only seen from the visible symptoms, namely the attitudes and behavior it displays. Furthermore, religion also concerns issues related to the inner life of humans. Basically every human being has the nature to be religious. Because religion is a basic human need. Psychology is very helpful in explaining the ways or steps for inculcating religious values, this is because before instilling religious values ​​in humans, it is better to be conditioned first. Thus, the psychology of religion has a very influential urgency in human life, both individually and in groups or in society. Based on these problems, the formulation of the problem is what is meant by psychology of religion. What is the function of the psychology of religion and what is the urgency of the psychology of religion? From the results of the literature review, it can be concluded that the psychology of religion is one of the disciplines that discusses or studies the influence of religious beliefs on a person's attitudes and behavior. There are several functions of the psychology of religion in society, including functioning as educative, savior, as reconciliation, social control, fostering a sense of solidarity, as normative, creative and sublimative. As for some of the urgency of the psychology of religion in the new perspective, it is for mental health, the role in development, keeping a person in behavior, making religious teachings a healer.